2023
DOI: 10.1002/adfm.202305204
|View full text |Cite
|
Sign up to set email alerts
|

A Lean‐Zinc and Zincophilic Anode for Highly Reversible Zinc Metal Batteries

Abstract: Lean‐zinc anode is a promising configuration that can eliminate the trade‐off of energy density and cycle lifetime of zinc metal (Zn0) batteries. However, there are rare investigations of lean‐Zn anode designs and it remains a grand change to sustain high zinc reversibility under lean zinc conditions. Herein, a lean‐Zn anode design based on a hierarchical and zincophilic cobalt metal (Co0) nanowire‐decorated carbon host, which is derived from a ZnCo bimetallic organic framework, is reported. Within the lean‐Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…A full cell with a low N/P ratio of 1.34 displayed a high reversible capacity of 398.8 mAh g À 1 at 1 C and demonstrated excellent cycling stability. Li et al [57] further advanced the concept by carburizing a ZnCo bimetallic zeolitic imidazolate framework (ZnCo ZIFÀ L) and simultaneously reducing Zn 2 + and Co 3 + /Co 2 + into metallic Zn and Co, creating a low-Zn, layered, and zincofillic anode structure (Figure 7e). Previous studies have indicated that the reversibility of a metal anode highly depends on the lattice matching between the anode and its nucleation/growth matrix.…”
Section: Substrates Design For Electrodepositionmentioning
confidence: 99%
See 2 more Smart Citations
“…A full cell with a low N/P ratio of 1.34 displayed a high reversible capacity of 398.8 mAh g À 1 at 1 C and demonstrated excellent cycling stability. Li et al [57] further advanced the concept by carburizing a ZnCo bimetallic zeolitic imidazolate framework (ZnCo ZIFÀ L) and simultaneously reducing Zn 2 + and Co 3 + /Co 2 + into metallic Zn and Co, creating a low-Zn, layered, and zincofillic anode structure (Figure 7e). Previous studies have indicated that the reversibility of a metal anode highly depends on the lattice matching between the anode and its nucleation/growth matrix.…”
Section: Substrates Design For Electrodepositionmentioning
confidence: 99%
“…(Reproduced with permission. [57] Copyright 2023, Wiley-VCH.) lattice match with Zn metal, avoiding local charge accumulation issues resulting from an incoherent interface.…”
Section: Substrates Design For Electrodepositionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the cycling performance of Zn anodes, coating an artificial protective layer on the zinc anodes is commonly used, which effectively homogenizes the zinc plating/stripping process. [9,[16][17][18][19][20][21][22][23][24][25] For example, Zhou et al synthesized nitrogendoped graphene on the surface of zinc foil and achieved good cycling performance at a DOD of 36% for 178 cycles. [26] In another work, Zhao et al created a zincophilic metal-organic framework (MOF) modified layer on Zn foil, which resulted in prolonged cycling at a DOD of 54% for over 700 h. [27] Nevertheless, due to severe volume change and irreversible zinc loss, the inevitable structural damage can easily result in the breakdown of the artificial protective layer, thus stable performance can only be achieved at low current density with low Zn utilization.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the cycling performance of Zn anodes, coating an artificial protective layer on the zinc anodes is commonly used, which effectively homogenizes the zinc plating/stripping process. [ 9,16–25 ] For example, Zhou et al. synthesized nitrogen‐doped graphene on the surface of zinc foil and achieved good cycling performance at a DOD of 36% for 178 cycles.…”
Section: Introductionmentioning
confidence: 99%